2011
DOI: 10.1152/japplphysiol.00796.2010
|View full text |Cite
|
Sign up to set email alerts
|

Convective flow dominates aerosol delivery to the lung segments

Abstract: Most previous computational studies on aerosol transport in models of the central airways of the human lung have focused on deposition, rather than transport of particles through these airways to the subtended lung regions. Using a model of the bronchial tree extending from the trachea to the segmental bronchi (J Appl Physiol 98: 970-980, 2005), we predicted aerosol delivery to the lung segments. Transport of 0.5- to 10-μm-diameter particles was computed at various gravity levels (0-1.6 G) during steady inspir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 38 publications
3
35
0
Order By: Relevance
“…This result is qualitatively consistent with the predictions of a recent CFD model by Darquenne et al (9) using an idealized geometry of the human central airway tree and uniform specific ventilation among lung segments. Their results showed that the distal delivery of aerosol from the trachea to the lung segments was largely determined by the distribution on ventilation for Stokes numbers in the trachea less than 0.01.…”
Section: Uneven Aerosol Deposition In Lungsupporting
confidence: 91%
See 3 more Smart Citations
“…This result is qualitatively consistent with the predictions of a recent CFD model by Darquenne et al (9) using an idealized geometry of the human central airway tree and uniform specific ventilation among lung segments. Their results showed that the distal delivery of aerosol from the trachea to the lung segments was largely determined by the distribution on ventilation for Stokes numbers in the trachea less than 0.01.…”
Section: Uneven Aerosol Deposition In Lungsupporting
confidence: 91%
“…We then collect all sources of variability into a single expression that describes lobar deposition in Equation (6). To better compare these sources of variability across different subjects, we account for differences in overall dosing, lung size, centrality of deposition, and restate the expression in nondimensional, normalized form in Equation (9). After several simplifications, we decouple the sources of variability in Equation (15).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on what is known about the physics of aerosol deposition, it is likely that most of the variability in peripheral aerosol deposition among lobes, sub-lobes, or any set of peripheral lung regions, can be attributed to one of four distinct factors: 1) differences in regional ventilation; (1,137,138) 2) differences in how the aerosol and air distribute between branches in the series of bifurcations along the pathway feeding the region; (138) 3) variability in the amount of the aerosol that escapes the series of airways along that pathway; (139)(140)(141) and 4) variability in the amount of aerosol that reaches the periphery and is not exhaled. (142) Using the concept of aerosol concentration as the average mass in suspension crossing any point of the bronchial tree, a theoretical framework can be defined to quantify each of the factors that lead to heterogeneous aerosol deposition among lobes: (143) differences in lobar ventilation per unit volume (specific ventilation), uneven splitting of aerosol and air at bifurcations (bifurcation factor), differences in the fraction of aerosol deposited along the feeding airways (escape factor), and differences in the fraction of aerosol that reaches the periphery but escapes via exhalation (retention factor).…”
Section: Challengesmentioning
confidence: 99%